2011
DOI: 10.1203/pdr.0b013e3182115000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Insulin-Like Growth Factor I and Nutrition During Phases of Postnatal Growth in Very Preterm Infants

Abstract: Pronounced growth restriction (GR) occurs after very preterm birth. The interaction between IGF-I, nutritional intake, and growth was evaluated prospectively in 64 infants with a mean (SD) GA of 25.7 (1.9) wk. Blood sampling of IGF-I and measurements of weight, length, and head circumference were performed weekly until discharge. Daily calculation of nutritional intake was performed. Standard deviation scores (SDSs) for growth parameters defined two growth phases: GR phase (birth until lowest SDS) and catch-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
85
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 37 publications
7
85
1
3
Order By: Relevance
“…Circulating IGF-I has also been suggested to regulate adipose tissue growth and the differentiation of preadipocytes into adipocytes (18). The influence or effect of IGF-II has been more difficult to establish, though IGF-II mutations seem to affect lean mass and fat mass distribution in pigs (19).Circulating IGF-I and IGFBP-3 reflect the short-term growth velocity in very-low-birth-weight infants (20,21). In healthy pregnancies, cord serum IGF-I levels are related more to the size of the skeleton than to the degree of mineralization (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating IGF-I has also been suggested to regulate adipose tissue growth and the differentiation of preadipocytes into adipocytes (18). The influence or effect of IGF-II has been more difficult to establish, though IGF-II mutations seem to affect lean mass and fat mass distribution in pigs (19).Circulating IGF-I and IGFBP-3 reflect the short-term growth velocity in very-low-birth-weight infants (20,21). In healthy pregnancies, cord serum IGF-I levels are related more to the size of the skeleton than to the degree of mineralization (17).…”
mentioning
confidence: 99%
“…Circulating IGF-I and IGFBP-3 reflect the short-term growth velocity in very-low-birth-weight infants (20,21). In healthy pregnancies, cord serum IGF-I levels are related more to the size of the skeleton than to the degree of mineralization (17).…”
mentioning
confidence: 99%
“…In line with that, Okuma et al found that IGF I levels were associated with white matter organization (42). Interestingly, mean IGF I concentration was positively correlated to neurodevelopmental outcome during a period, from 30 to 35 wk postmenstrual age, when a surge in IGF I levels occurred and infants started growing after a phase of postnatal growth restriction (14,39). This may suggest that IGF I has to reach a certain level before it can enhance neurodevelopmental outcome.…”
Section: The Role Of Igf I In Neurodevelopmentmentioning
confidence: 53%
“…Until term age, these infants IGF I levels' are also positively correlated with their preceding as well as their subsequent weight gain, indicating higher previous as well as higher subsequent growth rate in those infants with higher IGF I levels (14).…”
Section: The Role Of Igf I In Growth and Body Compositionmentioning
confidence: 87%
See 1 more Smart Citation